English : An interanational approach : Teacher's guide 2 - Mertin, Patricia (Oxford : Oxford Univeristiy Press, 2010)
Providing methodology, templates, photocopiable worksheets, lesson plans and a CD with listening material, this teachers' guide will assist the day to day planning of English for students aged 11-16 of all abilities. Each guide contains lesson plans with suggestions for additional activities,rubrics for the writing assignments, full answers to the student book and workbook as well as a CD packed full of poetry, prose and non-fiction for listening and comprehension skill development which students of all ability levels will enjoy listening to.